IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT PERSPEKTIF EKONOMI ISLAM : Studi Kasus: Kelurahan Wijaya Pura Kota Jambi (Jurnal Riset Manajemen dan Akuntansi, 2023)
Implementation of the BPNT Program to improve people's welfare in an Islamic economic perspective, namely, distribution justice for fair distribution to all people who need it, halal food so that it conforms to halal principles and certification, management of riba-free transactions for program continuity, economic empowerment of recipients so that they are financially independent economy, and monitoring and accountability mechanisms in accordance with the principles of Islamic economics. The purpose of this research is to find, test, and develop insights regarding the implementation and effects of the BPNT Program in the Wijaya Pura Village, as well as to analyze the level of transparency of the program based on an Islamic economic perspective. The method used is descriptive qualitative. Techniques for checking the validity of data in qualitative research include credibility tests, transferability tests, dependability tests, and confirmability tests. The results of research on the BPNT Program in the Wijaya Pura Village are that this program has a positive impact on improving the welfare of the underprivileged through the distribution of food aid. Program implementation involves various stages, starting from the selection of beneficiaries to the direct distribution of funds.